New Zealand : Selected Issues and Statistical Tables. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper examines saving trends in New Zealand. The paper highlights that although national saving has risen since the early 1990s, it remains below the levels recorded in the early 1980s, and the increase has been insufficient to finance the additional investment expenditure that has been encouraged by the strong economic performance in recent years. Further, national saving in New Zealand remains below the Organization for Economic Cooperation and Development (OECD) country average, as it has been throughout the 1980s and 1990s. This paper also examines pension reform in New Zealand.